2022
DOI: 10.1007/s10796-021-10230-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Design Elements Affecting User Acceptance of Intelligent Agents: Past, Present and Future

Abstract: Intelligent agents (IAs) are permeating both business and society. However, interacting with IAs poses challenges moving beyond technological limitations towards the human-computer interface. Thus, the knowledgebase related to interaction with IAs has grown exponentially but remains segregated and impedes the advancement of the field. Therefore, we conduct a systematic literature review to integrate empirical knowledge on user interaction with IAs. This is the first paper to examine 107 Information Systems and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 129 publications
(172 reference statements)
1
13
0
Order By: Relevance
“…In the following, we will summarize key findings of articles. Elshan et al (2022) conduct a study entitled "Understanding the Design Elements Affecting User Acceptance of Intelligent Agents: Past, Present and Future " and present a systematic literature review of intelligent agents by studying the design elements affecting user acceptance. Intelligent agents are described as agents that perceive and respond in a timely manner and are capable of interacting with other agents (i.e., humans) and react to their environment.…”
Section: The Special Issuementioning
confidence: 99%
“…In the following, we will summarize key findings of articles. Elshan et al (2022) conduct a study entitled "Understanding the Design Elements Affecting User Acceptance of Intelligent Agents: Past, Present and Future " and present a systematic literature review of intelligent agents by studying the design elements affecting user acceptance. Intelligent agents are described as agents that perceive and respond in a timely manner and are capable of interacting with other agents (i.e., humans) and react to their environment.…”
Section: The Special Issuementioning
confidence: 99%
“…To identify a wide range of literature on CAs, the search string is chosen to be rather broad. Based on recent literature reviews (e.g., [6,7]), we identified different keywords researchers used to describe CAs. This resulted in the following search string: "conversational agent" OR "chatbot" OR "chat bot" OR "interactive agent" OR "talkbot"…”
Section: Paper Selection Processmentioning
confidence: 99%
“…However, the scientific literature is dispersed into different thematic axes and research areas [6,7]. Furthermore, the scientific and practical knowledge about CAs has also grown in a dispersed manner, given a shortage of integrative perspectives to support CA development and design processes [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ranjbartabar et al 15 reported in a study of virtual therapists presented on a computer screen that empathic virtual therapists might not necessarily deliver better emotional outcomes than neutral therapists. Overall, reviews of the use of virtual humans have highlighted the potential benefits of realisation of emotional behaviours in facilitating participant engagement 7 , 16 .…”
Section: Introductionmentioning
confidence: 99%